2005
DOI: 10.5558/tfc81548-4
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile response to conifer release alternatives on aspen-white spruce boreal mixedwood sites.Part II: Quality of aspen regeneration

Abstract: This study, a component of the Fallingsnow Ecosystem Project, was designed to investigate the effects of conifer release alternatives on the quality of regenerating trembling aspen (Populus tremuloides Michx.). A randomized block design was used to compare untreated aspen with aspen growing in areas treated with two broadcast cutting treatments (brushsaw and Silvana Selective) and two broadcast herbicide treatments (glyphosate and triclopyr). The glyphosate treatment virtually eliminated aspen, whereas triclop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…The result was the highest observed spruce height growth, with stem volumes and basal areas equivalent to trees that were more thoroughly released by the glyphosate treatment. Although top-killed aspen contained stem crooks seven years after treatment, relatively low levels of stem decay suggest that future volume production may not be significantly compromised (Greifenhagen et al 2005). As such, this treatment appears to temporarily reduce aspen height growth, allowing planted white spruce to maintain near-optimum growth, without jeopardizing the potential for the stand to pass through a productive mixedwood phase.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The result was the highest observed spruce height growth, with stem volumes and basal areas equivalent to trees that were more thoroughly released by the glyphosate treatment. Although top-killed aspen contained stem crooks seven years after treatment, relatively low levels of stem decay suggest that future volume production may not be significantly compromised (Greifenhagen et al 2005). As such, this treatment appears to temporarily reduce aspen height growth, allowing planted white spruce to maintain near-optimum growth, without jeopardizing the potential for the stand to pass through a productive mixedwood phase.…”
Section: Discussionmentioning
confidence: 99%
“…Without further treatment to reduce competition with the spruce, a single release cutting will likely produce deciduous-dominated mixedwoods as these stands mature. However, since approximately half of the aspen stems situated in the cut plots originated from cut stumps, concern for the future quality and merchantability of these stems is warranted (Greifenhagen et al 2005). Cutting aspen during peak growing season, when root reserves are low, and/or cutting with a higher stump has been shown to reduce root suckering and promote the development of low-vigour stump sprouts (Bell et al 1999), potentially allowing a mixedwood of more equal proportions to be established.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…in the Release treatment during field data collection showed that some individuals were not killed (Greifenhagen et al 2005). These individuals possess telltale "crooks" in their stems indicating Release induced rapid cell growth but not death.…”
Section: Discussionmentioning
confidence: 99%
“…For poplar, a cull factor of 30% for stems five to 75 years of age and 40% for stems older than 75 years was applied because poplar that re-sprouts after brush saw treatment is reported to be of lower quality (Greifenhagen et al 2005). White birch (Betula papyrifera Marsh.)…”
Section: Models and Model Inputsmentioning
confidence: 99%